Fosfoenolpiruvato carboxiquinase imobilizada: novos modelos de triagem de ligantes - Amaral, Bruno Sérgio do (2019)
Phosphoenolpyruvate carboxykinase (PEPCK) is a ubiquitous enzyme found in all known groups of organisms, acting in the reversible conversion of oxaloacetate (OAA) to phosphoenolpyruvate (PEP) and CO2, in the presence of divalent metal ion, and dependent of ATP or GTP. Their catalytic activity is usually measured by coupled assays with malate or pyruvate kinase/lactate dehydrogenases as preferred second enzyme. Thus, the PEPCK reaction product is converted by the action of a NADH-dependent enzyme, wherein the catalytic reaction is followed by the decrease in the absorbance at 340 nm due to the consumption of NADH. The main drawback in coupled assays is that any interference in the activity of the second enzyme will affect the result of the first enzyme. In addition, in the case of PEPCK, NADH has been reported as inhibitor of some of these enzymes. To overcome these problems, herein we report a direct assay to quantity PEP by liquid chromatography-tandem mass spectrometry (LC-MS). The difficulty related to PEPCK’s substrates and products are their higher hydrophilicity and poor retention in reverse-phase elution mode, which leads to coelution or low peak resolution. In spite of this, PEP was quantified in coelution with OAA by the differentiation obtained by the mass spectra data. The developed method was validated, and all the significant figures were in accordance with the adopted criteria. For that, PEPCK of T. cruzi was expressed as an active enzyme in Escherichia coli and purified by anionic exchanged and affinity chromatography. The method was used, then, to monitor the purification of T. cruzi PEPCK as well as to determine all the kinetics parameters of the purified enzyme. The direct method herein disclosed can be used for others PEPCKs. Moreover, a ligand fishing assay based on the immobilization of PEPCKs to magnetic particles was modulated based on a series of synthetic compounds that were screened towards PEPCKs using the solution activity assay here developed. In searching for selective binders, the affinity-based assay was used to screen four ethanolic extracts of Brazilian Cerrado plants: Qualea grandiflora, Diospyros burchellii, Anadenanthera falcata and Byrsonima coccolobifolia. The chemical characterization of the identified ligands was carried out by means of LC-HRMS analysis. These results are fully discussed. The efforts to produce a PEPCK immobilized capillary enzyme reactor to be used as a bioaffinity column in a flow assay is also presented.